Impact of COVID-19 on women and children and the need for a gendered approach in vaccine development. Issue 12 (1st December 2020) - Vora, Kranti Suresh; Sundararajan, Aarthi; Saiyed, Shahin; Dhama, Kuldeep; Natesan, Senthilkumar
ABSTRACT: The COVID-19 pandemic has imposed unprecedented health and socioeconomic challenges on public health, disrupting it on a global scale. Given that women and children are widely considered the most vulnerable in the times of emergency, whether in war or during a pandemic, the current pandemic has also severely disrupted access to reproductive and child health services. Despite this, data on the effect of the pandemic on pregnant women and newborns remain scarce, and gender-disaggregated indicators of mortality and morbidity are not available. In this context, we suggest the implementation of a gendered approach to ensure the specific needs of women and their newborns are considered during the development of COVID-19 vaccines. Taking into account gender-based biological differences, the inclusion of pregnant and lactating mothers in clinical trials for the development of COVID-19 vaccines is of vital importance.